Odpowiedź :
Odpowiedź:
a)
6 - 4(y - 3) = y
6 - 4y + 12 = y
-4y - y = -6 - 12
-5y = -18 /:(-5)
y = 18/5 = 3 3/5
b)
15z + 3(1 - 2z) = 9z
15z + 3 - 6z = 9z
9z - 9z = -3
0 = -3
rownanie sprzeczne
nie ma rozwiazan
Szczegółowe wyjaśnienie:
a) 6-4(y-3)=p
6-4(y-3)=y
6-4y+12=y
-4y-y= -6-12
-5y=-18/: (-5)
y=18/5=3 3/5
Równanie sprzeczne
b)15z+3(1-2z)=9z
15z+3-6z=9z
9z-9z=-3
Nie ma rozwiązań
6-4(y-3)=y
6-4y+12=y
-4y-y= -6-12
-5y=-18/: (-5)
y=18/5=3 3/5
Równanie sprzeczne
b)15z+3(1-2z)=9z
15z+3-6z=9z
9z-9z=-3
Nie ma rozwiązań